MASKULINITAS DAN STANDAR KECANTIKAN PADA IKLAN MS GLOW FOR MEN “SEMUA JUGA BISA” - Citra Rani Angga Riswari; Didik Sugeng Widiarto (Pusat Studi GESI - UWP, 2022)
In Indonesia, the use of facial care products for men is still considered as a taboo. Normalizing the use of facial care products for men is a form of challenge to the concept of toxic masculinity. MS Glow for Men, an Indonesian facial care product especially created for men, has released a video ad titled “Semua Juga Bisa